PETS, PURPOSE, AND PAIN MANAGEMENT: PERSPECTIVES FROM COMMUNITY-DWELLING ADULTS AGED 70+ YEARS - Janevic, M (Innov Aging, 2018)
Guidelines for treating persistent pain in older adults recommend cognitive-behavioral strategies to minimize pain’s impact on functioning and quality of life. These techniques include engaging in social and physical activity, distraction, and relaxation. Companion animals may facilitate these activities. We present findings from an ongoing focus group study with dog and cat owners aged 70+ years who have chronic pain that impairs functioning. Participants were identified via community flyers and a registry of potential research participants. Thematic analysis of the initial focus group (n=9 participants) reveals that pets provide a sense of daily purpose (“My dog makes me get off the couch”) and motivate adherence to an activity routine “even on bad days.” Some participants reported that their pets can detect pain exacerbations and provide extra comfort. After completing additional focus groups, study findings will inform a new cognitive-behavioral model of human-animal interaction for chronic pain management in older adults.